Konteks Wacana dalam Novel Raja Kate Dikepung Asap Karya Abel Tasman - Agusni, Jehan Pratiwi; Fatmawati (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
A good understanding of the context of the discourse will help someone in understanding the overall content of a novel. Therefore, this research is motivated by the importance of understanding the context of discourse. The problem in this research is what is the physical context, epistemic context, linguistic context, and social context in Abel Tasman's novel Raja Kate Dikepung Asap? This study aims to describe, analyze, interpret, and conclude the physical context, epistemic context, linguistic context, and social context in Abel Tasman's novel Raja Kate Dikepung Asap. The theory used to analyze the research problem is the theory of "discourse analysis" proposed by Sumarlam (2008). The approach in this research is a qualitative approach with content analysis method. Based on the results of data analysis, it was found data on the types of contexts consisting of physical context, epistemic context, linguistic context, and social context in Abel Tasman's novel Raja Kate Dikepung Asap. The physical context that states the place in Abel Tasman's novel Raja Kate Dikepung Smoke mostly discusses the Bukit Barisan forest and the kingdom in a dark hole called the Batang Lubuh Kingdom. The epistemic context found in Abel Tasman's novel King Kate Is Surrounded by Smoke relates to Cunding and Suparta's shared knowledge of Kate's people and ruling a kingdom. The linguistic context found in Abel Tasman's novel Raja Kate Dikepung Asap relates to the grammatical and lexical aspects found in the novel which contains a lot of pronouns. The social context found in Abel Tasman's novel Raja Kate Dikepung Asap relates to the relationship between Cunding and Suparta as cousins, Kintaro and Suparta as friends.